Control of Accounts Receivable Against Cash Flow At Outsourching Company PT. Pesat Jaya Persada - Hurriyaturrohman, Hurriyaturrohman; Mukhlis, Ade; Indupurnahayu, Indupurnahayu; Sundarta, M. Imam (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
The purpose of this study is how companies can control accounts receivable in order to create good cash flow records and avoid losses in the outsourcing company PT Pesat Jaya Persada Bogor. This research method will use data analysis techniques with the Miles and Huberman interactive model, this model starts from collecting raw data, displaying data, reducing data, and getting to data verification and conclusions. The results of the study in 2020 amounted to 4.07%, in 2021 amounted to 3.12% and in 2022 amounted to 3.49% and above the Industry standard of 2.2% and it can be said that the gross profit margin is healthy. In 2020 the Return On Assets result was 6.88%, in 2021 it was 2.92%, in 2022 it was 4.87% above the industry standard of 2.2%, concluding that the company is healthy. From the processing results of the Return On Equity Ratio (ROE) in 2020 amounting to 2.68%, in 2021 amounting to 2.27%, in 2022 with a result of 3.21%, this is above the existing industry standard of 2.5%. declared healthy. . In the calculation of the net profit margin in 2020 of 2.61%, in 2021 it reached 2.64%, in 2022 it reached 2.959% or the industry standard is above 2.6% and if rounded up, it is 2.6% or declared healthy. The calculation results of the current ratio report in 2020 amounted to 9.4%, in 2021 amounted to 7.9%, and in 2022 amounted to 7.2% and above the average industry standard of 1.5% declared healthy. In the quick ratio report in 2020 amounting to 5.8%, in 2021 amounting to 4.9% and in 2022 amounting to 4.4% declared healthy. In 2020 with a cash ratio result of 11.9%, 2021 amounted to 9.2%, in 2022 Cash amounted to 1.3% and the information was declared still in a healthy state. Suggestions for leaders need to emphasize the credit policy carried out, namely offering credit policies to prospective customers or users of security or cleaning services, by maintaining professionalism by determining the amount to be received and the credit payment period. To control finances and provide input to add new customers to increase the revenue that has been achieved.